Biokonsentrasi Timbal Dan Kadmium Terhadap Penaeus merguiensis Dalam Air Dan Sedimen Di Perairan Desa Sungsang I - Ita Emilia; Yunita Panca Putri; Jumingin Jumingin; Syamsul Rizal; Rangga Rangga (Universitas PGRI Palembang, 2022)
Sungsang Village is located at the mouth of the Musi River making this area dense with settlements and transportation activities, this contributes to damage and results in decreased water quality. This study aims to analyze the concentrations of Pb and Cd in water, sediment and white shrimp (Penaeus merguiensis) and examine the level of accumulation of Pb and Cd through the BCF values of Pb and Cd in white shrimp (Penaeus merguiensis) in water and sediment in the waters of Sungsang I Village. Results the study showed that the average concentration of Pb in water in the waters of Sungsang I Village was 0.104 mg/L, exceeding the threshold value in Kep.Minister of State for the Environment No. 51 of 2004. The average Pb content in sediments is 24.892 mg/Kg, still below the quality standards of the Guidelines for the Protection and Management of Aquatic Sediment Quality in Ontario. The average concentration of Pb in jerbung shrimp is 0.809 mg/Kg, this value exceeds the limit set by BPOM. The results of the Cd test showed that the average water content, sediment, and jerbung shrimp were 0.013 mg/L, 0.174 mg/Kg and 0.127 mg/Kg. The BCF Pb value of shrimp-sediment was 7.779 and BCF Pb of shrimp-sediment was 0.033. The BCF Cd of shrimp-sediments was 9.769 and the BCF Cd of shrimp-sediments was 0.730. The Pb and Cd bioconcentration values of the jerbung shrimp (Penaeus merguiensis) in water and sediment are included in the low accumulative category, because the BCF value is <100.